Evaluation and comparison of the sensitivity of three commercial RT-qPCR kits used for the detection of SARS-CoV-2 in Santiago, Chile - Roberto Luraschi; Álvaro Santibáñez; Carlos Barrera-Avalos; Eva Vallejos-Vidal; Eva Vallejos-Vidal; Eva Vallejos-Vidal; Carlos Mateluna-Flores; Javiera Alarcón; Javiera Cayunao; Andrea Mella-Torres; Felipe Hernández; Ailen Inostroza-Molina; et al. (Frontiers Media S.A., 2022)
IntroductionThe COVID-19 pandemic is still in force, causing global public health challenges and threats. Although vaccination and herd immunity have proven to be the most efficient way to control the pandemic, massive and early testing of patients using the RT-qPCR technique is crucial for constant genomic surveillance. The appearance of variants of SARS-CoV-2 with new mutations can reduce the efficiency of diagnostic detection. In this sense, several commercial RT-qPCR kits have been the target of extensive analysis because low assay performance could lead to false-negative diagnoses.MethodsIn this study, we evaluated the performance of three commercial RT-qPCR kits; Thermo Fisher (TaqMan 2019-nCoV Assay Kit v1), BGI and Roche (LightCycler® Multiplex RNA Virus Master) used for the diagnosis of COVID-19 throughout the pandemic in Santiago de Chile.ResultsUnder our best assay conditions, we found significant differences in Cq amplification values for control and viral probes, against the same nasopharyngeal swab samples (NPSs). In addition, in some cases, the sensitivity of the RT-qPCR kits decreased against viral variants.ConclusionOur study suggests evaluating the RT-qPCR kits used to detect SARS-CoV-2 because variants such as Omicron, which has several mutations, can compromise their detection and underestimate viral circulation.